2002
DOI: 10.1192/bjp.180.3.270
|View full text |Cite
|
Sign up to set email alerts
|

Islington study of dementia subtypes in the community

Abstract: Alzheimer's disease is confirmed as the most common cause of dementia in older people, followed by vascular dementia. However, DLB and FLD occur sufficiently often to be seen frequently in clinical practice and should be incorporated into future editions of standard diagnostic criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
129
1
10

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(145 citation statements)
references
References 29 publications
5
129
1
10
Order By: Relevance
“…Three of six United Kingdom population-based studies of late-onset dementia included information on subtype diagnoses (Alzheimer's disease, VaD or mixed dementia and "other") (48-50). A more recent communitybased study (51) provided information on the relative frequency of a wider range of subtypes; Alzheimer's disease (41%), VaD (32%), dementia in Parkinson's Disease (3%), FTD (3%) and DLB (8%); Only the EURODEM meta-analysis of studies in the 1990s provided gender-as well as age-specific proportions with Alzheimer's disease and VaD (37). In that study, while the proportion with Alzheimer's disease among females remained constant at around 70%, among men the proportion increased progressively from 38% among those aged 65-69 years to 80% in those over 90 years of age.…”
Section: Reviewmentioning
confidence: 99%
“…Three of six United Kingdom population-based studies of late-onset dementia included information on subtype diagnoses (Alzheimer's disease, VaD or mixed dementia and "other") (48-50). A more recent communitybased study (51) provided information on the relative frequency of a wider range of subtypes; Alzheimer's disease (41%), VaD (32%), dementia in Parkinson's Disease (3%), FTD (3%) and DLB (8%); Only the EURODEM meta-analysis of studies in the 1990s provided gender-as well as age-specific proportions with Alzheimer's disease and VaD (37). In that study, while the proportion with Alzheimer's disease among females remained constant at around 70%, among men the proportion increased progressively from 38% among those aged 65-69 years to 80% in those over 90 years of age.…”
Section: Reviewmentioning
confidence: 99%
“…Alzheimer disease accounts for 31% of those with dementia, presenting with short-term memory decline, language dysfunction, neuropsychiatric features, and, in 5% of cases, parkinsonism. [47][48][49] Dementia with Lewy bodies accounts for approximately 11% of patients with dementia and can present with falls or depression, which are also seen in Alzheimer disease; fluctuating dementia; and the more discriminatory presentations of visual hallucinations, multiple features, and, in 41% of cases, parkinsonism. Of note, the clinical features of parkinsonism in both forms of dementia are less severe than those seen in idiopathic Parkinson disease, presenting commonly with rigidity and bradykinesia and infrequently with resting tremor.…”
Section: Dementia With Lewy Bodiesmentioning
confidence: 99%
“…The proportion of FTD in relation to organic dementia in the present study was compared with the results from other studies [7,9,13,15,36,[43][44][45][46][47] (table 3). There were three population studies, of which two were based on patients admitted to clinics [7,9].…”
Section: Proportion Of Ftd In Relation To Organic Dementiamentioning
confidence: 89%
“…There were three population studies, of which two were based on patients admitted to clinics [7,9]. The remaining study identified subtypes of dementia in a representative community by screening persons directly in their homes [47]. The diagnostic criteria of FTD were commonly the Lund-Manchester criteria [1] except for two studies [46,47] that used the revised clinical version of Neary et al [3].…”
Section: Proportion Of Ftd In Relation To Organic Dementiamentioning
confidence: 99%